Vertical distributions of tropospheric formaldehyde, nitrogen dioxide, ozone and aerosol in southern China by ground-based MAX-DOAS and LIDAR measurements during PRIDE-GBA 2018 campaign. (1st April 2020) - Luo, Yuhan; Dou, Ke; Fan, Guangqiang; Huang, Shan; Si, Fuqi; Zhou, Haijin; Wang, Yujun; Pei, Chenglei; Tang, Fuying; Yang, Dongshang; Xi, Liang; Yang, Taiping; et al.
Abstract: As the development of megacities, combined air pollution has been of increasing concern in China, which is composed by primary pollution, such as Nitrogen dioxide (NO2 ), and the followed secondary pollution under certain meteorology circumstances and high concentration of precursors, such as tropospheric ozone, formaldehyde (HCHO) and fine particles. During PRIDE-GBA 2018 Campaign (Particles, Radicals, Intermediates from oxiDation of primary Emissions in Great Bay Area), we performed the high resolution vertical observations of pollution gases and aerosol, which are significant but scarce indexes in studying the mechanisms of tropospheric pollution, using remote sensing techniques. NO2 and HCHO column densities and vertical profiles are reconstructed from data of multi-axis differential optical absorption spectroscopy (MAX-DOAS). Tropospheric ozone profile and aerosol extinction are retrieved by the differential absorption light detection and ranging (LIDAR) system. In order to verifying the accuracy, we evaluated the consistency and reliability of MAX-DOAS and LIDAR measurements. The results showed reasonable agreement with in-situ and off-line observations at Canton Tower. A typical combined pollution process from Sep 29 to Oct 10 was analyzed in detail. More than 200 μg/m 3 tropospheric ozone in this case was considered from the anthropogenic sources, including industry, power plant, residential and transportation. The high emission from local industry and polluted air transport from northeast brought the main precursors of this pollution process. The photochemical formation of tropospheric ozone was turned into a VOC-limited regime on polluted days. Highlights: Vertical distribution of NO2, HCHO and aerosol were derived by MAX-DOAS. High resolution tropospheric ozone profiles were observed by LIDAR. Validations were performed using in-situ and off-line data at Canton Tower. As high as 300 μg/m 3 ozone was observed at Guangzhou during the campaign.